1980
DOI: 10.2527/jas1980.503472x
|View full text |Cite
|
Sign up to set email alerts
|

Valine Requirement of the Lactating Sow

Abstract: An experiment was conducted using production and metabolic criteria to estimate the valine requirement of the lactating sow. Ground corn, gelatin, corn sugar, vitamins, minerals and indispensable amino acids were used to formulate a diet containing all the essential nutrients except valine. L-valine was added to provide .23 (basal), .38, .53, .68 and .83% valine. Twenty-five mature Landrace x Yorkshire sows were randomly assigned to the five dietary treatments. Milk production and average pig weight gain incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Several publications are available on the requirement of sows on lysine, sulphur‐containing amino acids or threonine ( Speer , 1990; Kirchgessner et al., 1992, 1993; Schneider et al., 1992a,b; Schwarz et al., 1993; Paulicks et al., 1998; Westermeier et al., 1998). Those dealing with valine (Val) are either inconsistent or recommend Val concentration between 5.3 g/kg ( Rousselow and Speer , 1980) and 12.0 g/kg ( Moser et al., 2000) in the feed of lactating sows. To verify these recommendations the effects of graded Val supply on the performance of lactating sows were examined.…”
Section: Introductionmentioning
confidence: 99%
“…Several publications are available on the requirement of sows on lysine, sulphur‐containing amino acids or threonine ( Speer , 1990; Kirchgessner et al., 1992, 1993; Schneider et al., 1992a,b; Schwarz et al., 1993; Paulicks et al., 1998; Westermeier et al., 1998). Those dealing with valine (Val) are either inconsistent or recommend Val concentration between 5.3 g/kg ( Rousselow and Speer , 1980) and 12.0 g/kg ( Moser et al., 2000) in the feed of lactating sows. To verify these recommendations the effects of graded Val supply on the performance of lactating sows were examined.…”
Section: Introductionmentioning
confidence: 99%
“…The lactation requirement for some amino acids determined by the Iowa group were: 30 g per day for lysine (Lewis and Speer, 1973); 3.9 g per day for tryptophan (Lewis and Speer, 1974a); 23 g per day for threonine (Lewis and Speer, 1975b); 21 g per day for isoleucine (Naught and Speer, 1977); 25 g per day of leucine (Rousselow et £[., 1979) and 29 to 39 g per day for valine (Rousselow and Speer, 1980). In general these lactations studies were conducted during a 21 day lactation period.…”
Section: Amino Acid Studiesmentioning
confidence: 99%
“…In another study (Young et_ al., 1972), valine plasma levels were measured to assess the requirement of valine for humans. Studies of valine metabolism and its interaction with the other branched chain amino acids have been conducted with rats (Reeds, 1974;Oldendorf and Szabo, 1976;Shinnick and Harper, 1977); with poultry (Boldizsar, et al., 1973); and with humans (Nakagawa et ^., 1975) Requirement recommendations for valine have been reported for different animal species: poultry (Zimmerman and Scott, 1965), rats (McLaughlan and Illman, 1967;Stockland et aj_., 1970), growing pigs (Mitchell et 3%., 1968), pregnant swine (Rippel, 1967), lactating sows (Rousselow and Speer, 1980), growing kitten (Hardy et , 1977), green sea turtle (Wood and Wood, 1977), and also for man (Rose et a]^. » 1965).…”
Section: Valinementioning
confidence: 99%
See 1 more Smart Citation
“…Essential amino acid requirements for lactation studies have reported a similar trend (Lewis and Speer, 1973;Lewis and Speer, 1974a, b;Rousselow et al, 1979). However, in a study to determine the valine requirement for lactation, Rousselow and Speer (1980) (Sauberlich and Salmon, 1955) and chicks (Gray et al, 1960;Hill and 01 sen, 1963) has shown that dietary amino acid deficiencies result in reduced plasma concentration of that amino acid. Using mongrel dogs, Longenecker and Hause (1959) stated that changes in the plasma amino acid concentration after a meal is dependent upon the amino acid composition of the protein ingested.…”
Section: Plasma Urea Nitrogenmentioning
confidence: 90%